A project feasibility study of Rainbow Dormitory - Reago, Maricris A.; Bautista, Moanna Ayessa M.; Capones, Heide; Labarda, Louremel; Sabinada, Medilyn; Vista, Jay Alexis B.
A. Name of Business-- The business will be named and registered at the Department of Trade and Industry as Rainbow Dormitory. It is named as such because the building will be painted with the shades of the seven primary and complementary colors, thus having an easy and strong recall to people. -- B. Location. The proposed dormitory will be located in Candahug, Palo, Leyte, which is nine (9) kilometers away from Tacloban City, the region's capital. It is within the Regional Government Center and in-between the newly opened Academic Learning Center and National Food Authority, along the National Highway. The proponents of this project chose the location because it is adjacent to the Academic Learning Center where the primary target markets are set up. The market study, shows that students prefer a dormitory near their school, preferably walking distance. The site of the dormitory is just along the highway; making it easier to find transportation and thus, accessible. Passersby could be easily identify and distinguish the center. With this, less promotion is needed. -- C. Descriptive Definition of the Project-- Education is next to the military program of the Macapagal-Arroyo's administration because priority of the consideration as a key to economic, political, and social growth. In line with of the national government's aim of promoting quality education, the Leyte Provincial Government extended, support by coming up with various academic-enhancing institutions, particularly the private ones, could lease substantial space to hold offices and classes. This center is built to give aid to academic institutions and maximize learning. Tacloban City is known as the center for education, trade and agencies in region VIII, a total of eighteen (18) tertiary schools in the region, according to 2000 RSET survey. Presently, advances and progress has reached the nearest town, which is Palo, Leyte. Palo is now a continuously emergent government offices/agencies and schools situated in the municipality. Many establishments crop up along the area of Palo like the Academic Learning Center. Some prospect schools that would transfer in the ALC are STI, ABE, AMA Computer Learning Center (ACLC) and Holy Spirit Foundation (HSF). These campuses are currently located at the downtown area of Tacloban City. After conducting a market survey, the proponents have found out that students studying in these institutions came from nearby towns of Region VIII like Samar, N. Samar, E. Samar, and S. Leyte and are currently living in boardinghouses and in relatives' houses. This comprise 51.5% of the student population in the target schools. Out of the 6,401 student population, 3,297 live in boarding houses and in their relatives' house. Most of the students prefer that their boardinghouses/homes are close to their respective campuses, as what resulted in the survey where 74% of 254 students answered yes when asked about moving to a new boardinghouse near ALC, this means that if their school would transfer to ALC, they would also find a place nearest to it.